Unilever’s Sales and Promotion Strategies to Boost the Plant-Based Sales Performance of Carrefour in Spain - Elisa Febriany (iBuss Management, 2022)
In the past few years, the world food system has been in jeopardy with lots of hunger, food waste, emissions, and health issues. In 2020, a worldwide crisis and national lockdowns had caused a reorientation of priorities and the popularity of plant-based food products. Unilever wanted to address these issues and opportunities through the plant-based acceleration projects with Carrefour, starting with the 6 chosen European Countries. Unilever wanted to start in Spain as a try-out country before rolling out the strategies to the other G6 countries. This paper aims to suggest for Unilever drive plant-based sales performance with the recommended marketing, sales, and promotion strategies. In-depth research was conducted on internal and external conditions that might affect the projects. The writer interviewed the key people in charge of the projects to obtain the current performance (internal analysis). Both primary and secondary research was also being done to get the market landscape of the Spain market in terms of the plant-based to get an overview of the potential (external analysis). The writer proposed a comprehensive marketing, sales, and promotion plant to boost the plant-based sales performance in Spain and the blueprint for the other countries.Keywords: Marketing, Sales and promotion, Plant-based